ChemInform Abstract: Three Practical Approaches for the Synthesis of Novel 4, 7‐Dihetarylpyrazolo[1, 5‐a][1, 3, 5]triazines. Issue 12 (14th March 2013) - Insuasty, Henry; Insuasty, Braulio; Castro, Edison; Quiroga, Jairo; Abonia, Rodrigo; Nogueras, Manuel; Cobo, Justo
Abstract Best results are achieved by reaction of S, S‐diethyl thiocarbonates (I) with aminopyrazoles (II) under neat conditions and microwave irradiation.